62. Idiopathic trigeminal sensory neuropathy and fosmn syndrome. Despite a dissimilar disease course do they share common pathophysiological mechanisms?. Issue 1 (January 2015) - Leone, C.; Pennisi, E.; Biasiotta, A.; Antonini, G.; La Cesa, S.; Stefano, G. Di; Piroso, S.; Pepe, A.; Raffa, S.; Sommer, C.; Truini, A.; Cruccu, G.
<x xml:space="preserve">Abstract</x> Patients presenting with idiopathic bilateral trigeminal hypoesthesia may go on to have idiopathic trigeminal sensory neuropathy, a benign purely trigeminal neuropathy, or facial-onset sensory motor neuronopathy (FOSMN), a malignant life-threatening condition. No diagnostic criteria can yet differentiate the two conditions at their onset. Nor is it clear whether the two diseases are distinct entities or share common pathophysiological mechanisms. Seeking pathophysiological and diagnostic information to distinguish these two conditions at their onset, in this neurophysiological and morphometric study we neurophysiologically assessed function in myelinated and unmyelinated fibres and histologically examined supraorbital nerve biopsy specimens with optic and electron microscopy in 13 consecutive patients with recent onset trigeminal hypoesthesia and pain. The disease course distinctly differed in the 13 patients. During a mean 10 year follow-up whereas in eight patients the disease remained relatively stable, in the other five it progressed to possibly life-threatening motor disturbances and extra-trigeminal spread. From two to six years elapsed between the first sensory symptoms and the onset of motor disorders. In patients with idiopathic trigeminal sensory neuropathy and in those with FOSMN neurophysiological and histological examination documented a neuronopathy manifesting with trigeminal nerve damage selectively affecting myelinated fibres, but sparing the Ia-fibre-mediated proprioceptive reflex. Although no clinical diagnostic criteria can distinguish the two conditions at onset, neurophysiological and nerve-biopsy findings specify that in both disorders trigeminal nerve damage manifests as a dissociated neuronopathy affecting myelinated and sparing unmyelinated fibres thus suggesting similar pathophysiological mechanisms.